QUALITY OF LIGHT PORK SAUSAGES CONTAINING KONJAC FLOUR IMPROVED BY TEXTURIZING INGREDIENTS - A. Akesowan (Journal of Animal and Plant Sciences, 2013)
Texturizing ingredients including -carrageenan, polydextrose, oat bran and corn flour, at 0.5 and 1% addition level, were investigated for quality improvement of light pork sausages made with konjac flour. The addition of polydextrose and oat bran showed significant decreases (p<0.05) in cooking loss of the sausages with respect to the control sausage. Whilst, all texturizing ingredients at least 0.5% significantly increased (p<0.05) the sausage firmness, in exception of that with 0.5% oat bran. The lowest values for lightness (L*) and redness (a*) were observed for the sausage with 1% oat bran; on the contrary, the sausage with 1% -carrageenan displayed the highest lightness and yellowness (b*). Higher sensory scores for firmness and cohesiveness were evident when all texturizing ingredients were applied. The lowest juiciness score was obtained in the light sausage with 1% -carrageenan whereas that with polydextrose showed the lowest flavor. However, color scores obtained in all light sausages with texturizing ingredients were significantly lower (p<0.05) than the control.
Keywords: Konjac flour; sausage processing; low-calorie foods; texturizing ingredient